John U. Monro : Uncommon Educator - Capossela, Toni-Lee (Book collections on Project MUSE., 2012)
In 1967, John U. Monro, dean of the college at Harvard, left his twenty-year administrative career at that prestigious university for a teaching position at Miles College - an unaccredited historically Black college on the outskirts of Birmingham, Alabama. This unconventional move was a natural continuation of Monro's life-long commitment to equal opportunity in education. A champion of the underprivileged, Monro embodied both the virtues of the Greatest Generation and the idealism of the civil rights era. His teaching career spanned more than four decades, and, as the biographer shows in this book, Monro's influence reached well beyond his lifetime. In addition to being a talented administrator, Monro was a World War II veteran, a crusading journalist, a civil rights proponent, and a spokesman for the fledgling Peace Corps. His dedication to social justice outlasted the fervor of the 1960s and fueled bold initiatives in higher education. This book is a tribute to this passionate teacher and an affirmation of how one person can inspire many to initiate positive and lasting change.